Densification, Microstructure and Properties of 90W-7Ni-3Fe Fabricated by Selective Laser Melting - Junfeng Li; Zhengying Wei; Bokang Zhou; Yunxiao Wu; Sheng-Gui Chen; Zhenzhong Sun (Metals, 2019)
The preparation of refractory tungsten and tungsten alloys has always been challenging due to their inherent properties. Selective laser melting (SLM) offers a choice for preparing tungsten and tungsten alloys. In this work, 90W-7Ni-3Fe samples were prepared by selective laser melting and investigated. Different process parameter combinations were designed according to the Taguchi method, and volumetric energy density (VED) was defined. Subsequently, the effects of process parameters on densification, phase composition, microstructure, tensile properties, and microhardness were investigated. Nearly a full densification sample (≥99%) was obtained under optimized process parameters, and the value of VED was no less than 300 J/mm3. Laser power had a dominant influence on densification behavior compared with other parameters. The main phases of 90W-7Ni-3Fe are W and γ-(Ni-Fe), dissolved with partial W. In addition, 90W-7Ni-3Fe showed a high tensile strength (UTS = 1121 MPa) with poor elongation (<1%). A high average microhardness (>400 HV0.3) was obtained, but the microhardness presented a fluctuation along building direction due to the inhomogeneous microstructure.